Choosing the Correct Radiologic Test Case-Based Teaching Files - Lee, Susanna I.; Thrall, James H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
With the rapid growth in the cost of imaging and political and market pressures to contain health care costs, physicians are being encouraged to order only appropriate radiologic exams and to rationalize their choices. The American College of Radiology (ACR) Appropriateness Criteria have emerged as a widely accepted standard by which the appropriate use of radiologic exams is judged. This book is designed to enable physicians and trainees to learn the ACR recommendations in a clinically relevant and intellectually stimulating way. More than 400 clinical scenarios are organized into ten modules based on organ systems. Each scenario is addressed by means of an interactive quiz in which the reader is invited to select the best option from a number of imaging modalities. Each choice is given a numerical rating of appropriateness, with accompanying comments when necessary. Correlative images of pathologies are included to enhance the reader$1 (Bs appreciation of the diagnostic power of the modality in question. This book is ideal as a tool both for self-study and for quantitative evaluation of students$1 (Bknowledge.s
Choosing the appropriate radiologic exam: Plain film. Fluoroscopy. Ultrasound. Computed tomography. Magnetic resonance imaging. Nuclear medicine -- Breast imaging -- Cardiac imaging -- Gastrointestinal imaging -- Musculoskeletal imaging -- Neurologic imaging -- Pediatric Imaging -- Thoracic imaging -- Urologic imaging -- Vascular imaging -- Women$1 (Bs imaging.s
Keywords: Medicine; Emergency medicine; Obstetrics; Radiology, Medical; Internal medicine; Pediatrics; Medicine & Public Health; Imaging / Radiology; Internal Medicine; Emergency Medicine; Primary Care Medicine; Pediatrics; Obstetrics/Perinatology.